Relative Importance of Well-Being Determinants in Atlantic Canadian Families During the Pandemic - Taylor G. Hill MA; Jessie-Lee D. McIsaac PhD; Magdalena Janus PhD; De-Lawrence Lamptey PhD; Melissa D. Rossiter PhD; Joan Turner PhD (SAGE Publishing, 2023)
Framed by the socio-ecological model of well-being, we examined the relative importance of factors contributing to three dimensions of well-being (child, parent, and family) during the COVID-19 pandemic. A sample of 536 participants from the Atlantic provinces of Canada answered a cross-sectional survey in 2021, covering experiences during the pandemic (eg, changes in family life and well-being). Well-being was assessed with 3 single-item measures on positive change in the life of children, parents, and families during the pandemic. This study involved 21 predictor variables (eg, change in time spent on various family activities). Using multiple regression and measures of relative importance based on the Lindeman, Merenda and Gold (lmg) method, we identified the variables most important to predicting well-being. Twenty-one predictors accounted for 21% of the variance in child well-being, 25% in parent well-being, and 36% in family well-being. Well-being at all 3 levels (child, parent, and family) shared the same top predictor (family closeness). The top 6 predictors of well-being at each level were related to leisure (eg, play) and time-use (eg, to prepare meals, engage in self-care, and rest). The effect sizes were smaller for child well-being than at the parent or family level, suggesting there may be important predictors of child well-being not accounted for in these analyses. This study may inform family-level programing and policy that seeks to promote well-being for children and their families.